Membangun Sikap Moderat Berbasis Nilai Pesantren di Pesantren Al Islah Bondowoso - Salam, Miftahus (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
The focus of the research in this article is to find out and analyze the cultural values of Islamic boarding schools in shaping the moderate character of students, and the conditioning carried out. The method used is a qualitative approach and a case study type of research. Data collection techniques include walking, in-depth interviews, participant observation, and documentation studies. Data analysis techniques are carried out by condensing data, presenting data, and drawing conclusions. The results of the research state that the Islamic boarding school cultural values at the Al-Islah Bondowoso Islamic Boarding School are a combination of Tasamuh, Tawazun, I'tidal, Tawasuth, and Standing Above All Groups. Where this value was adopted from the Gontor Islamic Boarding School. Conditioning is carried out in several ways, namely the students are placed in multicultural rooms and not only from one region, communication uses Arabic and English, use of social space to strengthen moderate character, and the example of Kyai and ustadz.